THE PROFILE OF STUDENTS MISTAKES IN ANSWERING FUNCTION LIMIT QUESTIONS AND ALTERNATIVE SOLUTION TO OVERCOME THE PROBLEMS - Sudirman Sudirman (Universitas Negeri Makassar, 2013)
This is an explorative research which explores profile of students’ mistake in answering function limit questions at SMA Negeri 15 Makassar. Subject of the research consisted of 20 students divided in 5 student on hight group, 10 students on fair group and 5 students on low group. The aimed of this research showed that the kinds of mistakes is the error on concept included error on function limit. The error principles whish existed were the errors on the usage of limit theory, the usages of trigonometry formula, the usage of conjugate multiplication principle, and error on the usage of write off principle. The errors os strategy included the fault on the steps to solve the function limit question. The technical errors included counting error, did not follow the instruction of questions, error of factoring, and the used calculator. The reasons of the error were: (1) the used of calculator in calcilating, (2) mistakes in understanding the theory, (3) influenced on the steps to solve yhe unction limit quetions, (4) did not understand certain form, (5) presumed a concept of principle based on experiences, (6) did not read and give attention to the intruction of the question, (7) fault on generalizing limit theory, (8) forgrt on such formula or feature, (9) did not comprehend the conjugate multiplication principle, (10) did not comprehend the write off principle on fraction, calculation, multiplication, and subtraction, (11) difficult to do factoring, (12) did not comprehend steps in solving the limit quetions, (13) mistakes on calculating, and (14) nerousness in doing the questions due to the time loss. Alternative to overcome the mistakes by students was by communicate their mistakes through interview by: (1) reminding students things they already forget, (2) explaining things that they did not undertand, (3) giving a concrete example disclaim the usage of wrong concept or principle, and (4) giving them advice to inprove their study. The result of Chi Square revealed that there is no correlation between the level of students’ ability with the kids of mistakes in answering questions of function limit of class XI-IA students at SMA Negeri 15 Makassar